(untitled) (Bulletin KNOB, 2008)
In 1769 the parents of Abraham van der Hart (1747-1820) divorced. His father found new employment as master carpenter in Nijmegen in the east of the Netherlands. Abraham, twenty-two years old, stayed in Amsterdam, probably with his mother and in the next years took over the businesses of his father, among which his building firm. In 1771 the young Van der Hart was one of the advisors of the vroedschap (town council) of Weesp for the building of a new town hall. As a carpenter he made a plan for rebuilding the existing town hall, whereas Libero Druck made a design for a completely new building. Eventually at the end of the year Jacob Otten Husly received the assignment for the whole project. Both Libero Druck and Jacob Otten Husly were acquainted with the latest developments of French architecture and provided severe classical designs. For Van der Hart this was perhaps his first acquaintance with this new Louis XVI style. Of the three designs which can be attributed to him two of them were rather traditional, but one of them already had a more classical aspect.